2018
DOI: 10.1186/s40942-018-0137-8
|View full text |Cite
|
Sign up to set email alerts
|

Eplerenone in the treatment of central serous chorioretinopathy: a review of the literature

Abstract: PurposeThe purpose of this review is to examine the role of eplerenone in the treatment of central serous chorioretinopathy (CSCR).MethodsA comprehensive search of the PubMed database has been conducted regarding eplerenone for CSCR, while studies using spironolactone were excluded. Articles and book chapters cited in the reference lists of articles obtained by this method were reviewed and included when considered appropriate, while the retrieved articles were filtered manually to exclude duplicates.ResultsOr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Therefore, eplerenone should no longer be recommended in patients with CSC. Results from previous studies showed that only 33% of the eyes treated with eplerenone achieved complete resolution of SRF after 6 weeks of therapy [9,10]. Our results suggest a treatment success of SRT in 2 of 3 eyes in patients with acute persistent CSC.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Therefore, eplerenone should no longer be recommended in patients with CSC. Results from previous studies showed that only 33% of the eyes treated with eplerenone achieved complete resolution of SRF after 6 weeks of therapy [9,10]. Our results suggest a treatment success of SRT in 2 of 3 eyes in patients with acute persistent CSC.…”
Section: Discussionsupporting
confidence: 49%
“…Besides "watchful waiting" for 3 months, a systemic therapy with eplerenone can be applied. Eplerenone 25 mg/day is given for 1 week and 50 mg/day for about 6 weeks after potassium lab control by the general practitioner [9]. In some studies, nearly one-third of patients showed a complete resolution after a median of 106 days under eplerenone treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment modalities for CSCR generally target the RPE, choroid or both. They aim to improve the ability of the RPE to remove the subretinal fluid, to diminish leakage from the choroid vessels, or to decrease fluid flux across the RPE barrier [3] . Management usually involves either waiting for spontaneous resolution, which commonly occurs within 3 months of onset or the use of focal laser photocoagulation, photodynamic therapy with verteporfin and anti-vascular endothelical growth factor (anti-VEGF) agents in cases of choroidal neovascularisation related to CSCR [4] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] High levels of endogenous (i.e., in Cushing's syndrome or in pregnancy) or exogenous (i.e., intra-articular, intranasal, systemic, or topical) corticosteroids, type A personality, abnormal coagulation and platelet aggregation, male gender, smoking, hypertension, and oxidative stress have been considered to be significant risk factors for the development of CSCR. [ 4 ]…”
mentioning
confidence: 99%
“…However, glucocorticoids cause an increased expression of ocular mineralocorticoid receptors (MR)[ 6 ] and act by binding both to the receptor for glucocorticoid and that for mineralocorticoid with equally high affinity. [ 4 ] Over activation of the MR in the choroidal endothelial cells induces upregulation of vasodilator potassium channels which modulates smooth muscle cells relaxation in the choroidal vasculature causing choroidal vasodilation and fluid accumulation in the retina. MR antagonists like spironolactone and eplerenone have been successfully used in the treatment of CSCR.…”
mentioning
confidence: 99%